Application of LADM for disaster prone areas and communities. (January 2019) - Unger, Eva-Maria; Zevenbergen, Jaap; Bennett, Rohan; Lemmen, Christiaan
Abstract: Disaster prevention, response and recovery require information about land tenure. Though, in many high-risk contexts, such records are non-existent or not up to date. As a result, vulnerable groups are often passed over by the government during risk management activities. At present there exists no dedicated tool for supporting land tenure recordation of all people-to-land relationships for the purposes of disaster risk management. More specifically, the required supportive data models and standards that could enable integration of concepts from the respective domains of land administration and disaster risk management are also lacking. Standardized data models could support software and service designs. This paper introduces a model linking the domains of land administration and disaster risk management – with the goal of supporting resilience against natural disasters and providing an approach for collecting data once, and using it multiple times. A design approach was used to develop the model – with adaption of the international Land Administration Domain Model (LADM) standard acting as a basis. Key features of the model include the support of interoperability through standardisation, the inclusion of all people-to-land relationships including those specific to disaster contexts, and the potential of the model to contribute to each of the disaster phases. The model is suggested to be highly applicable in natural disaster contexts where no land tenure information exists or the national mapping authority already uses a land administration system compatible with LADM. Overall, the model is considered as a step toward an implementable strategy for applying responsible land administration in the context of disaster risk management.